(untitled) (Journal of Contemporary Philology, 2022)
The text problematizes culture as a field of conflict of meanings, coding and decoding gender stereotypes in popular culture and different perspectives that initiate the critical potential of consumers of cultural products in recognizing subversive messages through representation of women in popular culture. The paper deals with the interaction between the text, the meaning, the context, the recipient and the discourse. Consequently, in an attempt to avoid the binary position of male-female relations and patriarchal models, it is crucial to recognize the problematic gender representation of women in popular culture which, in fact, nurtures normative gender roles in society that lead to sexism and discrimination. Through this analysis we will try to conclude that the production of meanings extends far beyond the processes of production, exchange and reproduction of culture.